Lysogeny in encapsulated and nontypable strains of haemophilus influenzae - Muthivhi., Tshlidzi (My University, 1991)
Limited information on the prevalence of lysogeny and the morphological features of bacteriophages in encapsulated and nontypable strains of Haemophilus influenzae is available from the literature. This study was conducted to investigate lysogeny in wild-type strains of H. influenzae and to characterize bacteriophages recovered from these clinical strains. Following induction by mitomycin C, 16 of 58 isolates of H. influenzae tested produced lysis. Addition of chloramphenicol inhibited cell lysis, indicating that protein synthesis was essential for induction. Type b capsules did not inhibit cell lysis or their ability to become lysoginized
A dissertation submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. 1991
Keywords: Lysogeny; Haemophilus influenzae; Bacteriophages